Phase reddening on near-Earth asteroids: Implications for mineralogical analysis, space weathering and taxonomic classification - Sanchez, Juan A.; Reddy, Vishnu; Nathues, Andreas; Cloutis, Edward A.; Mann, Paul; Hiesinger, Harald (Icarus (New York, N.Y. 1962), 2012)
► We studied the phase reddening on near-Earth asteroids and lab samples spectra. ► Phase reddening has no significant impact on the mineralogical analysis. ► Phase reddening is comparable to certain degree of space weathering. ► Phase reddening can lead to an ambiguous taxonomic classification. Phase reddening is an effect that produces an increase of the spectral slope and variations in the strength of the absorption bands as the phase angle increases. In order to understand its effect on spectroscopic observations of asteroids, we have analyzed the visible and near-infrared spectra (0.45–2.5μm) of 12 near-Earth asteroids observed at different phase angles. All these asteroids are classified as either S-complex or Q-type asteroids. In addition, we have acquired laboratory spectra of three different types of ordinary chondrites at phase angles ranging from 13° to 120°. We have found that both, asteroid and meteorite spectra show an increase in band depths with increasing phase angle. In the case of the asteroids the Band I depth increases in the range of ∼2°<g<70° and the Band II depth increases in the range of ∼2°<g<55°. Using this information we have derived equations that can be used to correct the effect of phase reddening in the band depths. Of the three meteorite samples, the (olivine-rich) LL6 ordinary chondrite is the most affected by phase reddening. The studied ordinary chondrites have their maximum spectral contrast of Band I depths at a phase angle of ∼60°, followed by a decrease between 60° and 120° phase angle. The Band II depths of these samples have their maximum spectral contrast at phase angles of 30–60° which then gradually decreases to 120° phase angle. The spectral slope of the ordinary chondrites spectra shows a significant increase with increasing phase angle for g>30°. Variations in band centers and band area ratio (BAR) values were also found, however they seems to have no significant impact on the mineralogical analysis. Our study showed that the increase in spectral slope caused by phase reddening is comparable to certain degree of space weathering. In particular, an increase in phase angle in the range of 30–120° will produce a reddening of the reflectance spectra equivalent to exposure times of ∼0.1×106–1.3×106years at about 1AU from the Sun. This increase in spectral slope due to phase reddening is also comparable to the effects caused by the addition of different fractions of SMFe. Furthermore, we found that under some circumstances phase reddening could lead to an ambiguous taxonomic classification of asteroids.